Kontekstualisasi Hak dan Keadilan melalui Eksepsi dalam Gugatan Rekonvensi Perkara Harta Bersama - Fikri, Fikri; Aris, Aris; Saidah, Saidah; Ramadhan, Nurul Fitra; Darwis, Rizal (Al-Mizan (e-Journal), 2023)
This study aims to explain the contextualization of rights and justice through exceptions in the counterclaim of marital property lawsuits in the Religious Court of Pinrang. The research method used is normative-legal qualitative research, with a document study to analyze Decision Number 703/Pdt.G/2021/PA Prg. Data analysis is conducted using legal enforcement theory and rights and justice theory. The research results indicate that maximizing exceptions in marital property lawsuits in the Religious Court of Pinrang ensures the protection of rights and justice for all parties involved in society. The context of responses, replies, and rejoinders during the examination of marital property cases is essential to respond to the claims and clarify disputes in society to safeguard the rights and justice of both the plaintiff and defendant. Exceptions in legal enforcement during the examination of cases allow the plaintiff and defendant to assess the validity of claims in the conventional lawsuit, while exceptions in the counterclaim provide an opportunity for the defendant to protect their rights and justice during the proceedings of marital property cases.